Performance of the Swede score to predict cervical intraepithelial neoplasia in women with HIV‐1 in Johannesburg, South Africa. Issue 2 (22nd October 2020) - Maringa, Vusumuzi David; Chikandiwa, Admire; Gilham, Clare; Mbodi, Langanani; Kelly, Helen; Mayaud, Philippe; Delany‐Moretlwe, Sinead; Adam, Yasmin
Abstract: Objective: To evaluate the performance of the Swede score to detect cervical intraepithelial neoplasia (CIN) in women with HIV‐1 in Johannesburg, South Africa. Methods: A cross‐sectional study using secondary data analysis from the HPV in Africa Research Partnership (HARP) study that compared the performance of three different screening tests to detect CIN. Colposcopy was performed on any woman who screened positive and findings were recorded using the Swede score. A biopsy of any lesion and a four‐quadrant biopsy was taken. The score was evaluated against a histological diagnosis of >CIN1. The sensistivity, specificity, PPV and NPV for each score was calculated. Results: Median age and CD4+ count of the 576 women eligible from the Johannesburg cohort was 34 years (IQR, 30–39) and 427 cells/mm 3 (IQR, 323–579), respectively. Almost two‐thirds (64%) were on ART and about 21% had CIN 2+ on histology. A Swede score of 5 or greater had the best combination of sensitivity and specificity for CIN 2+ with an AUC of 0.72 (95% CI, 0.68–0.76) corresponding to a sensitivity of 72.1 (95% CI, 63.5–79.6) and specificity of 71.8 (95% CI, 67.4–75.9). Conclusion: The Swede score can assist in determining whether women with HIV/AIDS should have treatment at the first colposcopy visit versus those who may be followed up, thereby individualizing treatment. Abstract : Colposcopy using the Swede score can be used to determine immediate versus delayed treatment, which in turn can be used to individualize treatment in women with HIV/AIDS.